Agronomic performance and grains quality of black bean genotypes - Marconato, Marcela Bonafin [UNESP]; Checchio Mingotte, Fábio Luiz [UNESP]; Coelho, Anderson Prates [UNESP]; Lemos, Leandro Borges [UNESP] (Centro Universitario de Maringa, 2021)
The evaluation of black bean genotypes in the various production environments and crop years is essential to indicate the most promising materials to producers and breeding programs. The objective of this study was to evaluate and compare the agronomic performance and grain quality of commercial cultivars and black bean lines grown in the winter season and to indicate the most promising genotypes within each group. The experiment was conducted over two agricultural years, in the city of Jaboticabal (SP), Brazil. The design used was a randomized block, with 14 treatments and three replications. The treatments consisted of black bean genotypes, four commercial cultivars (BRS Esplendor, BRS Campeiro, IPR Uirapuru, BRS 7762 Supremo) and ten lineages (CNFP 11973, CNFP 11976, CNFP 11978, CNFP 11979, CNFP 11983, CNFP 11984, CNFP 11985, CNFP 11991, CNFP 11994 and CNFP 11995). The variables evaluated were the components of production, productivity and grain quality. Data were subjected to analysis of variance (F test) and, when significant (p < 0.05), the means were grouped using the Scott and Knott test. The evaluated genotypes showed genetic variability for grain quality, being also influenced by the agricultural year. The BRS 7762 Supremo cultivar presents agronomic performance and grain quality well above other commercial cultivars. The CNFP 11983 lineage stands out from the others, presenting grain yield and cooking time similar to the commercial cultivar BRS 7762 Supremo, being recommended for further studies in breeding programs.
Desempenho agronômico e qualidade dos grãos de genótipos de feijão-preto
Keywords: Beanplant; Cooking time; Grain yield; Phaseolus vulgaris L